Policies for Regulating Partnership Relationships in Land Transport Businesses in The Era of The Industrial Revolution 4.0 - Agatha Jumiati; Esti Aryani; Erlin Suci Ikayani (Indonesian Journal of Law and Justice, 2025)
This study aims to examine how the policy of regulating partnership relationships in land transportation businesses in the Era of the Industrial Revolution 4.0. This research is motivated by the fact that currently in various parts of the world are facing the era of the industrial revolution 4.0. The presence of the industrial revolution 4.0 has been able to cause fundamental changes in various fields of human life, including in the field of labour law. There has been a shift in industrial relations from labour relations to partnership relations. This shift has the impact of causing problems related to the existence of workers such as welfare and legal protection of workers This research is a descriptive normative juridical research using secondary data and qualitative data analysis. The output of this research is in the form of mandatory output. Mandatory outputs are scientific publications planned to be published in Non-Scopus International Journals and presentation of research results at Refanas.The planned TKT is TKT 1 because in this study the goal to be achieved is to examine how the policy of regulating partnership relations in land transportation businesses in the Era of the Industrial Revolution 4.0. The results of this study indicate that the policy of regulating partnership relations in land transportation businesses in the Era of the Industrial Revolution 4.0 refers to Law Number 20 of 2008 concerning MSMEs. In practice in the field, the partnership relationship policy has not been implemented in a partnership agreement which must actually contain the principle of equality (Article 36 of Law Number 20 of 2008) and the principle of independence (Article 34 Paragraph (3) of Law Number 20 of 2008).